Protective effect of Kumquat fruits and carrot seeds extracts against brain aging in rats - Doha Abdou Mohamed; Karem Fouda; Ibrahim Mohamed Hamed; Sherein s. Abdelgayed (Shahrekord University of Medical Sciences, 2019)
Introduction: Protection of brain against accelerated aging helps avoiding the occurrence of neurodegenerative diseases. So, the current work was conducted to evaluate the rescuing role of kumquat fruits crude ethanol extract, carrot seeds ethanol and petroleum ether extracts against the brain aging induced by D-galactose in rats. Methods: Forty male Sprague Dawley rats were divided equally into five groups. Group I was served as normal control, rats of group II were daily injected intraperitoneally (i.p.) with 150 mg/kg BW of D-galactose. Rats of group III, IV and V were daily injected i.p. with the same dose of D-galactose and administered orally with 250 mg/kg BW/day of kumquat fruits crude ethanol extract, carrot seeds ethanol extract and carrot seeds petroleum ether extract, respectively. After 6 weeks the rats were scarified, brain tissues were analyzed for malondialdehyde (MDA), catalase (CAT) as well as histological examination. Also, the plasma was analyzed for MDA, tumor necrosis factor-α (TNF-α), creatinine and urea levels, as well as CAT, butyrylcholinesterase (BChE), aspartate transaminase (AST) and alanine transaminase (ALT) activities. Results: From the results, it was elucidated that the tested extracts suppressed both the reduction in CAT and the elevation in MDA either in brain or plasma and the increase in plasma TNF-α, BChE as well as liver and kidney parameters. Conclusion: The tested extracts can be served as potent protective agents against the accelerated aging parameters which may be due to anti-oxidant and anti-inflammatory activities.